ANALISIS WAKTU TUNGGU TERHADAP KEPUASAN PASIEN DI INSTALASI LABORATORIUM RUMAH SAKIT UMUM DAERAH DAYA KOTA MAKASSAR - Andi Niartiningsih; Nurul Hidayah Nur; Nurfitriani; Mene Paradilla; Muhammad Takqa; Iqbal Mochtar (Akademi Kebidanan Harapan Bunda Bima, 2026)
Patient satisfaction affects various aspects of hospital healthcare services, including both inpatient and outpatient care. Patient satisfaction can be defined as the condition experienced by patients after receiving services or treatment that meet their expectations. This study aimed to analyze the waiting time in relation to patient satisfaction at the laboratory installation of Daya Regional General Hospital. This research employed a quantitative approach using an analytical-descriptive observational design with a cross-sectional study. The study was conducted from May to June 2024 at Daya Regional General Hospital. The study population consisted of all patients who visited the hospital’s laboratory installation, totaling 16,151 patients in 2023. Based on the sample size calculation, the minimum number of respondents required for this study was 164. The findings showed that the average waiting time for services at the laboratory installation met the established standards. This was reflected by 265 patients (98.1%) who received services within the standard waiting time. In addition, a significant relationship was found between waiting time and patient satisfaction at the laboratory installation. These results indicate that the longer the waiting time experienced by patients, the greater the likelihood of dissatisfaction. Therefore, the findings demonstrate a clear pattern that waiting time is one of the factors influencing patient satisfaction.